Perfusion and Volume Response of Canine Brain Tumors to Stereotactic Radiosurgery and Radiotherapy. (5th May 2016) - Zwingenberger, A.L.; Pollard, R.E.; Taylor, S.L.; Chen, R.X.; Nunley, J.; Kent, M.S.
Abstract : Background: Stereotactic radiosurgery (SRS) and stereotactic radiotherapy (SRT) are highly conformal, high‐dose radiation treatment techniques used to treat people and dogs with brain tumors. Objectives: To evaluate the response to SRS‐ and SRT‐treated tumors using volume and perfusion variables and to measure the survival times of affected dogs. Animals: Prospective study of 34 dogs with evidence of brain tumors undergoing stereotactic radiosurgery (SRS) or stereotactic radiotherapy (SRT). Methods: Computed tomography and MRI imaging were used to calculate tumor volume and perfusion at baseline, and at 3 months and 6 months after treatment. Survival analysis was performed to evaluate treatment efficacy. Results: Mean tumor volume significantly declined from baseline to the first recheck by −0.826 cm 3 (95% CI: −1.165, −0.487) ( P < .001); this reduction was maintained at the second recheck. Blood flow and blood volume declined significantly in the tumor after treatment. Median survival was 324 days (95% CI: 292.8, 419.4), and 4 dogs survived longer than 650 days. Neither actual tumor volume (hazard ratio = 1.21, P = .19) nor the change in tumor volume from the baseline (hazard ratio = 1.38, P = .12) significantly affected the hazard of death because of the tumor. Conclusions and Clinical Importance: Stereotactic radiosurgery and SRT are effective treatments for reducing tumor volume, blood flow, and blood volume. Treated dogs surviving for more than 1 year are more likely to die from other causes than of their primary brain tumor. SRS and SRT should be considered for noninvasive treatment of intracranial brain tumors.